Black activists write Wheatley and Washington - O'Malley, Lurana Donnels, 1964- author. Link
1 online resource (282 pages)
Keywords: This book examines how early twentieth-century Black theatre artists depicted national mythologies of the United States.White-authored pageants and plays written for the 1932 Bicentennial celebration of George Washington's birthday relegated Black Americans to the periphery through racist stereotyping. Black activists Mary Church Terrell and W. E. B. Du Bois seized the opportunity to place Black people at center stage and to revise contemporary views of Washington and of Black achievement. Terrell's Historical Pageant-Play Based on the Life of Phyllis Wheatley and Du Bois's George Washington and Black Folk dramatize how the achievements of Black men and women fit into the US origin story. Terrell's script is a biography of the life of the enslaved African poet Phillis Wheatley; Du Bois's pageant is a transgressive revision of the Washington myth.The book's chapters contextualize these plays within the larger Bicentennial event. O'Malley also includes her edited version of Terrell's script, published here for the first time.This interdisciplinary book will be a valuable resource for college and university courses in American theatre and performance studies, Black Studies, and Women's Studies.